Implementation of Teaching English Students using the Index Card Match Method in Class VII MTS Ma'arif - Septiana Wandira; Salim Maulana (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
The index card match method is the delivery of material by using game cards to match cards that have been cut and contain a grid or short words according to the subject matter. Through Index Card Match, students are directed to understand and know the messages contained in the learning material. This study aims the use of application of the index card match method to improve the English vocabulary of seventh-grade students at MTs Ma'arif Karangasem. In this study, the researcher used qualitative research, there are primary and secondary data, primary data was obtained through interviews and field observations at the research site, while secondary data was obtained through file documents from MTs Ma'arif Karangasem. Based on data shows the improvement in students' language through the index card method used and their enthusiasm for learning, this can be seen through the language used by class VII students, namely 50% Indonesian and 50% English used.